Hepatitis B virus large surface protein is priming for hepatocellular carcinoma development via induction of cytokinesis failure1. Issue 1 (16th November 2018) - Musa, Julian; Li, Jing; Grünewald, Thomas GP
Abstract: Chronic hepatitis B virus (HBV) infection is a main risk factor for development of liver cirrhosis and hepatocellular carcinoma (HCC). Although HBV vaccination and antiviral therapy lead to substantial risk reduction for HCC development, it is evident that both can reduce, but not completely eliminate the risk. High serum levels of HBV surface antigen (HBsAg) were shown to predict disease progression of chronic HBV infection in patients harboring low viral load, and in line with this, HBV surface proteins were shown to exert oncogenic functions. As HBsAg seroclearance is infrequently achieved in patients who have undergone antiviral therapy, it is necessary to gain further insights into molecular mechanisms of HBsAg seroclearance failure after antiviral therapy and HCC development mediated by HBV surface proteins. A recent study published in this journal has shown that the HBsAg large surface protein (LHBs) contributes to HCC development by inducing cytokinesis failure and consequent aneuploidy via induction of DNA damage and polo‐like kinase 1 (PLK1)‐mediated G2/M checkpoint failure in hepatocytes. Inhibition of PLK1 by a PLK1‐specific small molecule inhibitor was shown to restore G2/M checkpoint in vitro and to reduce tumor burden in vivo . The initial LHBs‐induced hepatocyte aneuploidy may give rise to further aneuploidy and thereby lead to self‐propagating cycles of chromosomal instability driving intra‐tumor heterogeneity and clonal cancer evolution. Thus, LHBs‐induced cytokinesis failure may be a priming event for HCC development. In conclusion, the study not only provides further mechanistic insights into the oncogenic role of LHBs, but also identifies a potential target to interfere with the vicious circle of LHBs‐induced aneuploidy, which may be especially useful in patients showing failure of HBsAg seroclearance after antiviral therapy. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd. Abstract : Linked Article: Li et al J Pathol 2018;245: 502-513